(3GdCNdGb GdeJHhdjIs
(3ChdgG (B:s
(3SejJgG JcGdja ai Mb GdNhGU hGddg CYde Ke deG bGd LejY GdOYGg s
(3BNQgG (B:s
(3Cfg bGd eG Hbi Ydi hLg GdCQV dCf CMO ef Cgd GdSfI hGdLeGYI abGdh dg hdG adGf abGd aGWdYg HYV GdENhGf Ydi cQGS gPG GdcJGH Je GdcJGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs